Investigation of fatigue damage initiation and growth for composite wind tunnel model propeller blades - Nahuis, R.B.; Panis, T.M.; Hetebrij, M.; Grijpma, R.A. (SAMPE, 2025)
In order to understand the results from a high cycle fatigue test of a composite wind tunnel blade, a test campaign was performed with simplified test elements, representative for a typical composite blade. Next to monitoring the frequency drop for a fixed number of cycles as done in traditional high cycle fatigue testing, an alternative approach with a focus on phase response instead of frequency response was also studied. Multiple test elements were tested at different amplitudes, for at least several million cycles. Test elements were inspected after each test with in-house penetrant and ultrasonic C-scan inspection techniques. It can be concluded that using a 3% drop in eigenfrequency as a determination for fatigue initiation is questionable. It is clear that before a 3% drop in eigenfrequency is found, damage is already present in the elements. It was shown that changes in phase can be measured, before a significant change in eigenfrequency can be found.